Outcomes of therapeutic keratoplasty for severe infectious keratitis in Chongqing, a 16-year experience - Zhang Q; Zhao M; Xu M; Gu F; Liu Q; Chen Y; Zhang H; Kijlstra A (Infection and Drug Resistance, 2019)
Qi Zhang,1 Min Zhao,1 Mei Xu,1 Fengjuan Gu,1 Quan Liu,1 Yuan Chen,2 Haiqi Zhang,1 Aize Kijlstra31The First Affiliated Hospital of Chongqing Medical University, Department of Ophthalmology, Chongqing Key Laboratory of Ophthalmology and Chongqing Eye Institute, Chongqing, People’s Republic of China; 2Chongqing Vision Institute, Chongqing, People’s Republic of China; 3University Eye Clinic Maastricht, Maastricht, the NetherlandsPurpose: This study aimed to evaluate the outcomes of therapeutic keratoplasty for severe infectious keratitis in Chongqing (Southwest China).Patients and methods: The records of 561 eyes that underwent therapeutic keratoplasty for refractory microbial keratitis from 2001 to 2016 were analyzed in this retrospective study. Data included demographic information, microbiological investigations, associated factors, graft size, preoperative status, postoperative complications, and final anatomical outcomes.Results: Trauma was the most common cause (267, 47.6%) for corneal ulcers leading to therapeutic keratoplasty. The etiological diagnosis included bacterial keratitis (80 eyes, 14.3%), fungal keratitis (317 eyes, 56.5%), acanthamoeba keratitis (3 eyes, 0.5%), and mixed bacteria/fungal infection (15 eyes, 2.7%). Anatomical success was achieved for 492 eyes (87.7%), with bacterial keratitis having a better outcome than fungal and mixed infections. Diabetes and preoperative time ≥30 days were significantly associated with anatomical failure in the multivariate logistic regression (P=0.028 and P=0.022, respectively). Patients with hypopyon, corneal perforation, surgical delay, and/or large graft size had a higher incidence of postoperative complications (reinfection, cataract, glaucoma, hyphema, or graft rejection) (P<0.05).Conclusion: Therapeutic keratoplasty was an effective procedure in managing refractory infectious keratitis. Prompt and appropriate surgery would result in fewer complications and better outcomes.Keywords: therapeutic keratoplasty, infectious keratitis, corneal ulcer